Assessing The Commitment of Indonesian Government Towards Climate Change Policy: The Yudhoyono Presidency 2004-2014 [Menilai Komitmen Pemerintah Indonesia terhadap Kebijakan Perubahan Iklim: Pemerintahan Presiden Yudhoyono 2004-2014] - Lidya Christin Sinaga (Jurnal Politica, 2020)
As the largest archipelagic state and the world’s third-largest emitter of greenhouse gases, Indonesia’s commitment to climate change policy is critical. In 2009, Indonesia under President Susilo Bambang Yudhoyono showed its commitment by setting environmental targets, which included a commitment to reduce deforestation by decreasing the number of forest fires by 20 percent each year. The commitment, however, could not be fully realised. Unsurprisingly, in 2015 for the umpteenth time, a thick haze of smog caused by the forest fires blanketed Indonesia and its neighbours, Malaysia and Singapore. The pollution unavoidably raises uncertainty of Indonesia’s role in advancing the climate change regime. Since 85 percent of emissions in Indonesia come from deforestation, Indonesia’s failure to tackle this problem is a serious issue in relation to its international role. Indonesia’s international commitment and motivation then come into questions, particularly considering the country’s domestic conduct. While not dismissing the positive impacts of its active commitment, this paper evaluates climate change policy in Indonesia during the Yudhoyono administration by applying the context of multi-level governance, namely the impact of international, local government, and non-governmental actors in environmental policy. None should be in any doubt on the point that Yudhoyono has dealt with climate change issues more seriously than any previous president. However, since Indonesia falls behind on its national commitment, this paper argues that Indonesia’s role in establishing climate change regime is more driven by its international stature.AbstrakSebagai negara kepulauan terbesar dan penghasil emisi gas rumah kaca terbesar ketiga di dunia, komitmen Indonesia terhadap kebijakan perubahan iklim sangat penting. Pada tahun 2009, Indonesia di bawah Presiden Susilo Bambang Yudhoyono menunjukkan komitmennya dengan menetapkan target untuk mengurangi deforestasi dengan mengurangi jumlah kebakaran hutan sebesar 20 persen setiap tahun. Namun, target ini tidak sepenuhnya dapat diwujudkan. Pada tahun 2015 untuk yang kesekian kalinya, kabut asap tebal yang disebabkan oleh kebakaran hutan menyelimuti Indonesia dan tetangganya, Malaysia dan Singapura. Kasus ini menimbulkan ketidakpastian atas peran Indonesia dalam memajukan rezim perubahan iklim. Mengingat 85 persen emisi di Indonesia berasal dari deforestasi, kegagalan Indonesia untuk mengatasi masalah ini adalah persoalan serius terkait peran internasionalnya, apalagi dengan melihat implementasi pada tataran domestiknya. Meskipun tidak menampik dampak positif dari komitmen aktifnya, tulisan ini mengevaluasi kebijakan perubahan iklim di Indonesia selama masa kepresidenan Yudhoyono dengan menerapkan konteks tata kelola multi-level, yaitu dampak aktor internasional, pemerintah daerah, dan non-pemerintah dalam kebijakan lingkungan. Seharusnya tidak ada yang meragukan bahwa Yudhoyono telah menangani masalah perubahan iklim dengan lebih serius daripada presiden sebelumnya. Namun, melihat minimnya komitmen dan implementasi di tingkat nasional, peran Indonesia dalam membangun rezim perubahan iklim lebih tampak sebagai upaya membangun citra internasional.